Importance application discipline Yāma and Niyāma for yoga trainer in Bali - Widyastuti, Ni Putu; Lucky, Juliant Krisnaningtyas Divandka Savita (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Application discipline Yāma and Niyāma hold roles crucial for yoga trainers in Bali, good in development personal or professional. Yāma, which includes principles of ethics like ahimsa (without violence), satya (honesty), asteya (no stealing), brahmacharya (control self), and aparigraha (no greedy), purposeful For form moral character and integrity a yoga trainer. On the other hand , Niyāma, which consists from saucha (cleanliness), santosha (satisfaction), tapas (discipline), svadhyaya (study self), and Ishvara pranidhana (surrender to God), focuses on spiritual development and well-being inner. Practicing yoga trainer second principle This in a way consistent. Not only capable of creating an environment practice that is harmonious and conducive, but also plays a role as an example for his students. Method: This qualitative study examines how yoga trainers in Bali apply Yāma and Niyāma . Data were collected through in-depth interviews with 25 trainers, participatory observations, and documentation. Thematic analysis was used to identify and interpret key themes related to the application of these principles in teaching and personal development. Findings: Discipline Yāma and Niyāma help coach in controlling emotions, increase concentration, and maintain mental balance, which in turn increase quality yoga teaching. Additionally, implementation​ discipline also supports coaches in undergoing a healthy and sustainable, which is essential in maintaining stamina and energy positive. In Bali, it is known as a spiritual and cultural center, and applications to Yāma and Niyāma become more significant. Culture local rich with spiritual values are in line with the principles of yoga, so it makes it easier to coach For integrate discipline This in life daily. Conclusion: With internalization of Yāma and Niyāma , yoga trainers in Bali can enrich their spiritual experience, enhance professionalism, and deliver a more positive impact to the yoga community. Application discipline This Not only as moral rules, but as road comprehensive, reflective life​ harmony between body, mind, and soul. Novelty/Originality in this Study: This study crosses the line between ancient tradition and modern practice, revealing how the principles of Yāma and Niyāma translate into the lived realities of yoga instructors in Bali. By investigating the unique intersection of yoga philosophy, Balinese culture, and the global wellness industry, this study provides valuable insights into the adaptation and relevance of spiritual teachings in a contemporary context.